Early Axonal Dysfunction of the Peripheral Nervous System Influences Disease Progression of ALS: Evidence From Clinical Neuroelectrophysiology - Yu, Huiyan; Chen, Lu; Zhang, Shuo; He, Jing; Fan, Dongsheng (Frontiers in Neurology, 2021)
Studies have indicated that more axonal dysfunction in early ALS predictive of more aggressive phenotypes. However, as an important electrophysiological index to detect motor axonal damage, the prognostic value of compound muscle action potential (CMAP) in ALS remains unclear. Here we investigated if CMAP could be a prognostic indicator of disease progression in early ALS. OBJECTIVE To assess the prognostic value of the decrement in compound muscle action potential amplitude within 12 months of symptom onset (CMAP-12 amplitude) for the survival of patients with amyotrophic lateral sclerosis (ALS). METHODS Patients were stratified into 4 groups according to the decrement of the CMAP-12 amplitudes: normal (≥the lower limit of normal, LLN), mild (